End-of-life care content in postgraduate critical care nursing programs: Structured telephone interviews to evaluate content-informing practice. Issue 2 (March 2020) - Ranse, Kristen; Delaney, Lori; Ranse, Jamie; Coyer, Fiona; Yates, Patsy
Abstract: Background: The provision of end-of-life care remains a significant component of work for clinicians in critical care settings. Critical care nurses report that this area of practice receives limited attention in education and training. Objectives: The objective of this study was to identify and describe the end-of-life care content in postgraduate critical care nursing programs in Australia. Methods: Using a descriptive exploratory research design, an Internet search was undertaken in August 2015, identifying 17 education providers offering postgraduate critical care nursing programs. Thirteen individuals agreed to participate in a structured telephone interview regarding end-of-life content in their postgraduate program. Descriptive statistics were calculated to summarise the data obtained. Results: Twelve participants reported that end-of-life care content was explicitly addressed in their postgraduate critical care nursing programs, yet variation in actual content areas covered was evident. The majority of programs addressed content related to organ donation (92%) and legal and ethical issues (77%). However, content least commonly identified as covered pertained to the work of the nurse in providing direct clinical care to the patient at the end of life and his or her family, including the physical changes experienced by the dying patient (31%), respiratory management encompassing withdrawal of ventilation and symptom management (23%), emotional support of family (23%), care of the body after death (23%), and the process of withdrawing life-sustaining treatment (15%). Participants (92%) agreed that end-of-life content was important in postgraduate critical care nursing programs, with 77% of participants agreeing that more time should be allocated to end-of-life content. Conclusions: This study provides preliminary evidence of the variation in end-of-life content in postgraduate critical care nursing programs in Australia. Addressing gaps in end-of-life care content in formal education, including clinical care of the dying patient, is urgently needed to address the complexity of this phase of care that is so frequently provided in critical care units.